2021
DOI: 10.1093/femsml/uqab013
|View full text |Cite
|
Sign up to set email alerts
|

Patho-epigenetics: histone deacetylases as targets of pathogens and therapeutics

Abstract: In recent years the interplay of epigenetics and infection moved into the limelight. Epigenetic regulation describes modifications in gene expression without alterations of the DNA sequence. In eukaryotes, this mechanism is central for fundamental cellular processes such as cell development and differentiation, but it is also involved in more specific tasks such as the response to infection by a pathogen. One of the most common types of epigenetic changes is the modification of histones. Histones, the small pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…Bioinformatic analyses of the L. pneumophila strain Paris genome identified the gene lpp2163 encoding a 424 amino acid long protein, predicted to be a Zn 2+ -dependent histone deacetylase, that we named LphD ( L egionella p neumophila h istone D eacetylase) 12 . We computed a structural model of LphD using AlphaFold 23 which allowed prediction of the protein structure with high confidence ( Figure 1A ) except for the N- and C-terminal regions (amino acids 1-25 and 415-424), that are likely unstructured in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analyses of the L. pneumophila strain Paris genome identified the gene lpp2163 encoding a 424 amino acid long protein, predicted to be a Zn 2+ -dependent histone deacetylase, that we named LphD ( L egionella p neumophila h istone D eacetylase) 12 . We computed a structural model of LphD using AlphaFold 23 which allowed prediction of the protein structure with high confidence ( Figure 1A ) except for the N- and C-terminal regions (amino acids 1-25 and 415-424), that are likely unstructured in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of their activity is a complex, multilayer process depending, among others, on the subcellular localization and protein complex formation. Although several bacterial pathogens have been shown to impact histone acetylation/deacetylation during infection by acting on expression of eukaryotic HDACs or their localization 12 , until now only the Neisseria gonorrhoeae Gc-HDAC protein has been shown to induce an enrichment of H3K9ac, in particular at the promoters of pro-inflammatory genes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of their activity is a complex, multilayer process depending, among others, on the subcellular localization and protein complex formation. Although several bacterial pathogens have been shown to impact histone acetylation/deacetylation during infection by acting on expression of eukaryotic HDACs or their localization 12 , until now only the Neisseria gonorrhoeae Gc-HDAC protein has been shown to induce an enrichment of H3K9ac, in particular at the promoters of pro-inflammatory genes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Excitingly, it has been shown recently that different pathogens manipulate histone modifications mainly by secreting effector proteins targeting the nucleus, so-called nucleomodulins 8 . In particular, histone methylation and histone acetylation have been shown to be potent targets for a variety of pathogens to promote their replication in their host cells [9][10][11][12] . One of the pathogens described to modulate histone PTMs of its host cell is Legionella pneumophila, a facultative intracellular, Gram-negative bacterium that parasitizes free-living protozoa, but that is also the causative agent of a severe atypical pneumonia in humans, called Legionnaires' disease 13 .…”
mentioning
confidence: 99%
“…In addition, HDAC3 and HDAC6 inhibition exerts anti-inflammatory activity and reduces pro-inflammatory cytokine production, improves clinical symptoms by blocking the production of IL-6 and TNF-α, and ameliorates clinical signs in models of systemic lupus erythematosus and colitis ( 39 43 ). Moreover, several studies suggested the use of HDACi to treat viral infections since acetylation and HDACs are involved at different levels during pathogens infections ( 44 ). Vorinostat, for instance, has been shown to have antiviral properties and to suppress adenovirus gene expression and replication ( 45 , 46 ).…”
Section: Introductionmentioning
confidence: 99%